Analisis Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Home Saty Tamala Di Kelurahan Kalabahi Timur Kecamatan Teluk Mutiara Kabupaten Alor (Studi Kasus Pada Kantor Home Stay Tamala Di Kelurahan Kalabahi Timur Kecamatan Teluk Mutiara - Fanmakani, Eudia; Awang, Mesak Y.; Anigomang, Ferdinand Romelus; Maruli, Elia (Peneliti.net, 2023)
Consumer satisfaction is an emotional assessment of the consumer after the consumer uses a product where the expectations and needs of the consumer who uses it are met. In this study aims to determine the effect of service quality dimensions on consumer satisfaction, this type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. This study uses primary population data and the sample is consumers who have used lodging services at Home Stay Tamala Kalabahi, Alor Regency totaling 30 people. The statistical method used in this study is multiple linear regression. The results of this study show that: Partially the physical evidence variable has a significant value of 0.000 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H1 which states that partial physical evidence has a positive effect on consumer satisfaction at Tamala Kalabahi Home Stay Alor Regency. Partial reliability variable has a significant value of 0.002 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H2 which states that partial secarah reliability has a positive effect on consumer satisfaction at Tamala Kalabahi Home Stay, Alor Regency. The partial responsiveness variable has a significant value of 0.014 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H3 which states that partial responsiveness has a positive effect on consumer satisfaction at Tamala Kalabahi Home Stay, Alor Regency. The partial empathy variable has a significant value of 0.002 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H4 which states that partial empathy has a positive effect on consumer satisfaction at Tamala Kalabahi Home Stay, Alor Regency. The partial collateral variable has a significant value of 0.000 where this value is smaller than the alpha value of 0.05 so that the results of this study receive H5 which states that partial secarah guarantee has a positive effect on consumer satisfaction at Tamala Kalabahi Home Stay, Alor Regency. Simultaneously, the variables of physical evidence, reliability, responsiveness and empathy and assurance have a significant value of 0.000, where this value is smaller than the alpha value, namely H6, which states that the variables of physical evidence, reliability, responsiveness and empathy simultaneously have a positive effect on consumer satisfaction at Home Stay Tamala Kalabahi, Alor Regency.